Transient increase in symptoms associated with cytokine release in patients with multiple sclerosis. - Moreau, T; Coles, A; Wing, M; Isaacs, J; Hale, G; Waldmann, H; Compston, A (1996)
Fourteen patients with multiple sclerosis were treated with the humanized monoclonal antibody CAMPATH-1H which targets the CD52 antigen present on all lymphocytes and some monocytes; four also received anti-CD4 antibody. Lymphopaenia developed rapidly and was sustained for at least 1 year. In 12 patients, the first infusion of antibody was characterized by significant exacerbation or re- awakening of pre-existing symptoms lasting several hours. These clinical effects of antibody treatment correlated with increased levels of circulating cytokines. Peak levels of tumour necrosis factor (TNF)-alpha and interferon (IFN)-gamma occurred at 2 h, whereas the rise in interleukin-6 (IL-6) was significantly delayed and peaked at 4 h after starting antibody treatment. There was a decline in CH50, indicating complement activation. The neurological symptoms could not be attributed directly to pyrexia and were not provoked (in one patient) by an artificial rise in temperature. In the remaining two patients, a single pre-treatment with intravenous methylprednisolone (500 mg) prevented both the transient increase in neurological symptoms and the cytokine release. Our results, involving 14 intensively studied patients treated with humanized monoclonal antibodies, suggested that soluble immune mediators contribute to symptom production in multiple sclerosis; the mechanism remains uncertain but, on the available evidence, we favour the interpretation that cytokines directly affect conduction through partially demyelinated pathways.